EVALUASI PERFORMANS REPRODUKSI SAPI PERAH RAKYAT DAN KUALITAS SEMEN BEKU DI KECAMATAN SELUPU REJANG, REJANG LEBONG, BENGKULU - Brilian Putra Pamungkas; Heri Dwi Putranto; Endang Sulistyowati (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The objective of this research was to evaluate reproductive performance of dairy cows and frozen semen in Kecamatan Selupu Rejang, Kabupaten Rejang Lebong, Bengkulu. Data collection were conducted through interview method using quisioner. Secondary data were about quality analysis of frozen semen straw carried out in UPTD Puskeswan Curup. Primary data primer were collected from 7 respondents (with total 19 cows), including characteristics of farmers, age, education, farming experience, main job. Paramaters evaluated were reproduction performance, such as Calving Interval (CI), Days Open (DO) and Service per conception (S/C), and quality of frozen semen, Motility, Viability and Abnormality. Results of evaluation of reproduction performance of dairy cows in Kecamatan Selupu Rejang, Kabupaten Rejang Lebong showed that Calving Interval 13.79 month, Days Open 139.73 days and Service per Conception 1.58. Quality of frozen semen used were in qualifying the standards of motility (46.87%, viability (63.32%), and abnormality (2.97%).